ISSUES OF TRANSLATION OF TOPONYMS IN "BABURNOMA" - Mukhtasar Odiljonovna Muminova (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The article gives information about anthroponyms and toponyms in "Boburnoma". It appears in the first pages of the work. If the toponyms are structured according to the location of the geographical regions that Babur conquered, studied, and lived, the system of anthroponyms is somewhat more complex. The names of historical figures are structured according to classes and categories, such as relatives, cousins, officials, friends, rivals. This system itself also has internal divisions according to ethnicity, gender, region, political and domestic relations.